2016
DOI: 10.1111/jbg.12203
|View full text |Cite
|
Sign up to set email alerts
|

Half of 23 Belgian dog breeds has a compromised genetic diversity, as revealed by genealogical and molecular data analysis

Abstract: The genetic diversity in 23 dog breeds raised in Belgium was investigated using both genealogical analysis and microsatellite markers. Some of these breeds are native breeds, with only small populations maintained. Pedigree and molecular data, obtained from the Belgian kennel club, were used to calculate the inbreeding coefficients, realised effective population size as well as probabilities of gene origin and average observed heterozygosity. Inbreeding coefficients ranged from 0.8 to 44.7% and realised effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
(88 reference statements)
3
31
1
Order By: Relevance
“…The natural canine attributes of visual and olfactory acuity (Chen, Irwin, & Zhang, 2012;Tacher et al, 2005), speed and endurance (Huson et al, 2012;Kemp, Bachus, Nairn, & Carrier, 2005;Pasi & Carrier, 2003), guardianship, predatory nature (Akkad et al, 2015;Starling, Branson, Thomson, & McGreevy, 2013;Sundman, Johnsson, Wright, & Jensen, 2016), and their seemingly innate companionability with humans (Cagan & Blass, 2016;Fadel et al, 2016;Gacsi, McGreevy, Kara, & Miklosi, 2009;vonHoldt et al, 2017;Jakovcevic, Elgier, Mustaca, & Bentosela, 2010;van der Waaij, Wilsson, & Strandberg, 2008) have been exploited for thousands of years. However, in the pursuit of a distinct lineage, selection of breeding animals will unavoidably rely on a small source pool (Alam et al, 2012;Calboli, Sampson, Fretwell, & Balding, 2008;Kumpulainen et al, 2017;Pfahler & Distl, 2015;Streitberger et al, 2012;Wijnrocx et al, 2016). As such, dog breeds which perform similar tasks are frequently more closely related to each other than to breeds with different occupations, allowing for the visualization of phylogenetic breed clades sometimes segregating by broad behavior patterns (Parker et al, 2017;Vaysse, et al 2011;von Holdt et al, 2010;Parker et al, 2004;and Figure 2).…”
Section: Italian Dog Breedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural canine attributes of visual and olfactory acuity (Chen, Irwin, & Zhang, 2012;Tacher et al, 2005), speed and endurance (Huson et al, 2012;Kemp, Bachus, Nairn, & Carrier, 2005;Pasi & Carrier, 2003), guardianship, predatory nature (Akkad et al, 2015;Starling, Branson, Thomson, & McGreevy, 2013;Sundman, Johnsson, Wright, & Jensen, 2016), and their seemingly innate companionability with humans (Cagan & Blass, 2016;Fadel et al, 2016;Gacsi, McGreevy, Kara, & Miklosi, 2009;vonHoldt et al, 2017;Jakovcevic, Elgier, Mustaca, & Bentosela, 2010;van der Waaij, Wilsson, & Strandberg, 2008) have been exploited for thousands of years. However, in the pursuit of a distinct lineage, selection of breeding animals will unavoidably rely on a small source pool (Alam et al, 2012;Calboli, Sampson, Fretwell, & Balding, 2008;Kumpulainen et al, 2017;Pfahler & Distl, 2015;Streitberger et al, 2012;Wijnrocx et al, 2016). As such, dog breeds which perform similar tasks are frequently more closely related to each other than to breeds with different occupations, allowing for the visualization of phylogenetic breed clades sometimes segregating by broad behavior patterns (Parker et al, 2017;Vaysse, et al 2011;von Holdt et al, 2010;Parker et al, 2004;and Figure 2).…”
Section: Italian Dog Breedsmentioning
confidence: 99%
“…Additionally, seven local landrace populations, defined as distinct dog varieties unique to a specific geographic region with historically limited breeding populations, are included in this study. The latter are not recognized by any purebred canine registry but, nonetheless, may display a genetic pattern consistent with other purebreeds (Alam, Han, Lee, Ha, & Kim, 2012;Puja et al, 2005;Tanabe, 2007;Wijnrocx, Francois, Stinckens, Janssens, & Buys, 2016; Yoo et al, 2017), such as has been observed for one Italian regional population, the Fonni's Dog Dreger, Rimbault, et al, 2016;Sechi et al, 2016). By focusing our analyses on breeds with diverse phenotypes that have all originated in a single country, we aim to employ genetic data to expand upon historical breed formation accounts and define the modes by which humans have produced recognizable and diversified dog breeds.…”
mentioning
confidence: 99%
“…; Wijnrocx et al . ). More rarely, studies have considered dog breeds raised in different countries, analysing gene flow between national populations (Oliehoek et al .…”
Section: Discussionmentioning
confidence: 97%
“…The evolution of genetic variability based on the genealogies of purebred dogs has been studied in many breeds (Karjalainen & Ojala 1997;Leroy et al 2006;Calboli et al 2008;Leroy et al 2009;M€ aki 2010;Lewis et al 2015;Wijnrocx et al 2016). More rarely, studies have considered dog breeds raised in different countries, analysing gene flow between national populations (Oliehoek et al 2009;M€ aki 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding rates and effective population sizes vary across breeds (Wijnrocx, Francois, Stinckens, Janssens & Buys, 2016). The Saarloos Wolfhond simulated in this study is at the lower end of the effective population sizes and was chosen because typically outcrosses are initiated for such breeds.…”
Section: Discussionmentioning
confidence: 99%